2023
DOI: 10.1039/d2bm01836e
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of allopurinol to acute hyperuricemic mice via polymer microneedles for the regulation of serum uric acid levels

Abstract: Allopurinol (AP) is widely used to treat hyperuricemia which may cause severe side effects after oral administration. Alternative means for the treatment of hyperuricemia are demanded to simultaneously facilitate drug...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…78 The pyrazolopyrimidine structure is particularly alluring due to its synthetic feasibility and profound pharmacological significance. Several well-known drugs in the market incorporate the pyrazolopyrimidine nucleus, including zaleplon, 79 indiplon, 80 allopurinol, 81 dinaciclib, 82 ocinaplon, 83 pyrazophos, 84 and sildenafil. 85 Pyrazolopyrimidines showcase a diverse range of pharmacological properties, serving as cyclin-dependent kinase (CDK) inhibitors, 86 antibacterial agents, 87 antifungal agents, 88 anti-proliferative compounds, 89 as well as anti-leishmanial 90 and antiviral agents.…”
Section: Maos Of N- and O-containing Heterocyclesmentioning
confidence: 99%
“…78 The pyrazolopyrimidine structure is particularly alluring due to its synthetic feasibility and profound pharmacological significance. Several well-known drugs in the market incorporate the pyrazolopyrimidine nucleus, including zaleplon, 79 indiplon, 80 allopurinol, 81 dinaciclib, 82 ocinaplon, 83 pyrazophos, 84 and sildenafil. 85 Pyrazolopyrimidines showcase a diverse range of pharmacological properties, serving as cyclin-dependent kinase (CDK) inhibitors, 86 antibacterial agents, 87 antifungal agents, 88 anti-proliferative compounds, 89 as well as anti-leishmanial 90 and antiviral agents.…”
Section: Maos Of N- and O-containing Heterocyclesmentioning
confidence: 99%
“…An in vivo study demonstrated that the AP-loaded MN system can effectively reduce SUA levels, akin to oral administration but with lower side effects, which will be conducive to reducing the adverse reactions and improving the bioavailability of AP. The SUA levels can still be maintained at the therapeutic level (∼150 μmol L −1 ) even after 5 h. 28 However, the effective timeframe for regulating SUA levels using this MN system remains relatively limited, posing a challenge in meeting the daily requirements for long-term SUA level management.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, DMNs fabricated from PVP and polycaprolactone (PCL) were successfully applied as patches for the transdermal delivery of allopurinol in an in vitro and in vivo study with the purpose of acute hyperuricemia treatment. 32 Zeng et al (2022) successfully developed as-fabricated flexible MN dressings loaded with metformin and CaO 2 @polydopamine (CaO 2 @PDA) nanoparticles for antibacterial properties against both S. aureus and E. coli and accelerated diabetic skin-wound healing. 33 Moreover, Ruan et al…”
Section: Introductionmentioning
confidence: 99%